2016
DOI: 10.1039/c6ay01106c
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometry for the determination of oxidant activity

Abstract: This paper aims to describe a new approach to using potentiometry for determining oxidants in liquids and ozonized and chlorinated water, in particular.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…A balance of metabolic redox species comprising ROS and antioxidants maintain the cellular physiological metabolic functions in plants and animals at a steady state [ 4 ]. Due to both endogenous and exogenous causes, an imbalance of these redox species can lead to cellular oxidative stress [ 5 , 6 ]. To maintain physiological metabolic balance, the natural antioxidant defense system can inhibit the oxidation of ROS, thus preventing the release of free radicals [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A balance of metabolic redox species comprising ROS and antioxidants maintain the cellular physiological metabolic functions in plants and animals at a steady state [ 4 ]. Due to both endogenous and exogenous causes, an imbalance of these redox species can lead to cellular oxidative stress [ 5 , 6 ]. To maintain physiological metabolic balance, the natural antioxidant defense system can inhibit the oxidation of ROS, thus preventing the release of free radicals [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has been conducted in the development of non-invasive platforms for redox potential monitoring due to their desirability. For instance, Brainina et al, 2016 [ 5 ], demonstrated a gel impregnated with the K 3 [Fe(CN) 6 ]/K 4 [Fe(CN) 6 ] redox couple (RC) that was taped on the skin for monitoring oxidant and antioxidant activity. In their study [ 5 ], CV was employed to record the anodic and cathodic response of K 3 [Fe(CN) 6 ]/K 4 [Fe(CN) 6 ] RC relative to the concentration of the oxidants and antioxidants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Redox state of a given redox-active species quantitatively defined by the ratio of the oxidized (Ox) and reduced (Red) form is important in many areas of classical analytical chemistry such as potentiometry and coulometry [1,2], in chronoamperometry and voltammetry, as well as for the operation of the electrochemical sensors [3][4][5][6]. The system containing both components of a single redox couple Ox/Red has been studied under conditions of various voltammetric techniques [7][8][9][10][11][12][13], considering both reversible and quasi-reversible electrode reactions in order to understand voltammetric features and to find a method for determination of the concentration ratio of the two redox forms.…”
Section: Introductionmentioning
confidence: 99%
“…The potentiometric method is one part of the electrometry technique. This method uses the principle of measuring electrical potential using several electrodes [14], [15], [16], [17]. The working electrodes used in this technique can use carbon paste electrodes (CPE) which can be modified with a polymer film on its surface to increase its sensitivity and selectivity.…”
Section: Introductionmentioning
confidence: 99%